The Role of BMT KUBE Sejahtera 036 in Empowering Community Economy in Maccini Gusung, Makassar City, Indonesia - Mansyur, Abdurrahman; Hudaya, Nurul; Ali, Engku Muhammad Tajuddin Engku (Department of Sharia Financial Management, Institut Agama Islam Negeri Sultan Amai Gorontalo, Indonesia, 2021)
BMT KUBE Sejahtera 036 as an Islamic microfinance institution has not only economic functions but also social functions, which is empowering the community's economy. This study aims to determine the role as well as the supporting and inhibiting factors of BMT KUBE Sejahtera 036 in empowering the community's economy in Maccini Gusung. The research method used is a qualitative method with data analysis techniques from Miles and Hubberman which consists of reduction, data presentation, and conclusion. The results showed that BMT KUBE Sejahtera 036 played a role in empowering the community's economy through increasing customer income, enhancing the entrepreneurial spirit of the surrounding community through training and improving skills as well as providing the capital needs of MSMEs. The supporting factors of BMT KUBE Sejahtera 036 in empowering the community's economy are the right market and good service quality. In addition, programs or policies for extending payment terms and eliminating fines also increase public interest in accessing financing through this BMT. While the inhibiting factors are the lack of promotion, the emergence of other financial institutions, the implementation of financing procedures is not optimal, and the limited amount of capital.